Pengembangan Game Edukasi Gema Dengan Pendekatan Kontekstual Berbantu Adobe Animate Pada Materi Bentuk Aljabar (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
This study aims to develop educational game media with a contextual approach assisted by Adobe Animate on feasible and practical algebraic material. The type of research used is Research and Development (R&D) with the ADDIE development model which consists of five stages namely Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of 28 students from class VII-F of SMP NU 06 Kedungsuren. The data collection instrument used a media validation questionnaire sheet, a material expert validation questionnaire sheet and a student response questionnaire sheet. The data analysis technique used is descriptive quantitative. The results of this study are in the form of educational game media products with a contextual approach assisted by Adobe Animate on feasible and practical algebraic material. This is based on the percentage of media expert and material expert validation questionnaires of 90.22% and 90.79% with very good criteria and the percentage of student response questionnaires is 86.64% with very good criteria.
Keywords: Educational Game; Contextual Approach; Adobe Animate